2017
DOI: 10.1016/j.ymthe.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod and Teriflunomide Attenuate Neurodegeneration in Mouse Models of Neuronal Ceroid Lipofuscinosis

Abstract: CLN diseases are rare lysosomal storage diseases characterized by progressive axonal degeneration and neuron loss in the CNS, manifesting in disability, blindness, and premature death. We have previously demonstrated that, in animal models of infantile and juvenile forms of CLN disease (CLN1 and CLN3, respectively), secondary neuroinflammation in the CNS substantially amplifies neural damage, opening the possibility that immunomodulatory treatment might improve disease outcome. First, we recapitulated the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 34 publications
8
67
0
Order By: Relevance
“…Interestingly, one mechanism how Sn expression on microglia/macrophages contributes to disease progression is the suppression of CD8 1 CD1221 regulatory T-cells. In a recent study, the immune modulators fingolimod and teriflunomide, both approved for multiple sclerosis, substantially attenuated neuroinflammation and improved disease outcome in CLN1 and CLN3 models, giving hope for future clinical interventions (Groh, Berve, & Martini, 2017). Additional microglia/macrophagerelated mechanisms are likely to contribute to the amplification of neural damage, as an increased expression of proinflammatory neurotoxic cytokines and oxidative damage have been reported in the mouse models (Benedict, Sommers, & Pearce, 2007;Groh et al, 2016b;Wei et al, 2008;Xiong & Kielian, 2013).…”
Section: Neuronal Ceroid Lipofuscinosesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, one mechanism how Sn expression on microglia/macrophages contributes to disease progression is the suppression of CD8 1 CD1221 regulatory T-cells. In a recent study, the immune modulators fingolimod and teriflunomide, both approved for multiple sclerosis, substantially attenuated neuroinflammation and improved disease outcome in CLN1 and CLN3 models, giving hope for future clinical interventions (Groh, Berve, & Martini, 2017). Additional microglia/macrophagerelated mechanisms are likely to contribute to the amplification of neural damage, as an increased expression of proinflammatory neurotoxic cytokines and oxidative damage have been reported in the mouse models (Benedict, Sommers, & Pearce, 2007;Groh et al, 2016b;Wei et al, 2008;Xiong & Kielian, 2013).…”
Section: Neuronal Ceroid Lipofuscinosesmentioning
confidence: 99%
“…Treatment with the antineuroinflammatory, small molecule MW151 was shown to have some beneficial effects on disease characteristics in a CLN1 model (Macauley et al, 2014), whereas the immune suppressant CellCept/mycophenolate mofetil ameliorated some mild symptoms in young models of CLN3 disease (Seehafer et al, 2011). In a recent study, the immune modulators fingolimod and teriflunomide, both approved for multiple sclerosis, substantially attenuated neuroinflammation and improved disease outcome in CLN1 and CLN3 models, giving hope for future clinical interventions (Groh, Berve, & Martini, 2017).…”
Section: Neuronal Ceroid Lipofuscinosesmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that, while the higher doses (3 and 10 mg/kg) significantly reduced neuroinflammation as indicated by the accumulation and activation of Iba-1+ cells, there was an inverse correlation between the doses tested and both blood-brain barrier permeability and neuroinflammation. These doses have been previously reported to be therapeutic to treat other rodent models of neurological conditions, [61][62][63] although those studies utilized different strains of rats and modeled neurodegenerative diseases rather than trauma. Future mechanistic studies are required to determine why the higher doses (3 and 10 mg/kg) did not attenuate the BBB breakdown in our model of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…However, short-term administration of mycophenolate mofetil to patients with CLN3 disease did not show a clinical benefit [ 24 ]. A potential therapeutic benefit of the immunomodulatory compounds fingolimod and teriflunomide was demonstrated in mouse models of CLN1 and CLN3 disease [ 25 ]. Oral administration of fingolimod and teriflunomide reduced microgliosis, neuron loss, and brain atrophy in Ppt1 ko and Cln3 ko mice.…”
Section: Therapeutic Strategies: Preclinical Studies and Clinical Trimentioning
confidence: 99%